2022
DOI: 10.1172/jci.insight.150881
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of cerebrospinal fluid outflow after low-rate lateral ventricle infusion in mice

Abstract: The anatomical routes for the clearance of cerebrospinal fluid (CSF) remain incompletely understood. However, recent evidence has given strong support for routes leading to lymphatic vessels. A current debate centers upon the routes through which CSF can access lymphatics, with evidence emerging for either direct routes to meningeal lymphatics or along cranial nerves to reach lymphatics outside the skull. Here, a method was established to infuse contrast agent into the ventricles using indwelling cannulae duri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 58 publications
4
30
0
Order By: Relevance
“…Cavernous lymphatics may thus drain peri-venous efflux from their tributary cerebral veins (superficial and deep middle cerebral veins, and hypophyseal vein), and possibly from orbital veins (superior and inferior ophthalmic), into collecting scLNs and dcLNs. The nasopharynx provided a support to the most anterior lymphatic drainage from the cavernous sinus, in agreement with the recent observation that the nasopharyngeal route has a main role in the extracranial drainage of CSF outflow (Decker et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Cavernous lymphatics may thus drain peri-venous efflux from their tributary cerebral veins (superficial and deep middle cerebral veins, and hypophyseal vein), and possibly from orbital veins (superior and inferior ophthalmic), into collecting scLNs and dcLNs. The nasopharynx provided a support to the most anterior lymphatic drainage from the cavernous sinus, in agreement with the recent observation that the nasopharyngeal route has a main role in the extracranial drainage of CSF outflow (Decker et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…The cavernous sinus collects blood from the superficial and deep middle cerebral veins and the ophtalmic and facial regions (Haines, 2018). CSF drainage from this anterior region has been identified (Antila et al, 2017;Ma et al, 2017;Decker et al, 2021), but the lymphatic circuitry involved remained unknown because the anterior and middle fossae of the skull base are difficult to assess by classical immunohistological techniques. In humans, the dural lymphatic architecture remains largely undefined (Absinta et al, 2017;Ding et al, 2021), despite the potential interest of dural lymphatic imaging for the prognosis of neurological diseases.…”
Section: Introductionmentioning
confidence: 99%
“…4, A, E–G, and I–K ). The nasopharyngeal lymphatics were recently shown to mediate extracranial drainage of CSF outflow ( Decker et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The CAV collects blood from the superficial and deep middle cerebral veins and the ophthalmic and facial regions ( Haines, 2018 ). CSF drainage from this anterior region has been identified ( Antila et al, 2017 ; Ma et al, 2017 ; Decker et al, 2021 ), but the lymphatic circuitry involved remained unknown because the anterior and middle fossae of the skull base are difficult to assess by classic immunohistological techniques. In humans, noninvasive imaging of dural lymphatic is of interest for the diagnosis and prognosis of neurological diseases ( Absinta et al, 2017 ; Ding et al, 2021 ), and different MRI protocols to detect MLVs have been reported ( Absinta et al, 2017 ; Ringstad and Eide, 2020 ; Wu et al, 2020 ; Ding et al, 2021 ; Albayram et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The sinuses in the dura mater are the neuro-immunological interface where CNS-derived antigens accumulate and the local antigen presenting cells (APCs) prime patrolling T cells ( 7 ). Dural lymphatic vessels lining the sinuses collect CSF from the subarachnoid space and interstitial fluid (ISF) from the brain and drain via connections through the nasal-cribriform plate into the nasopharynx lymphatic vasculature ( 8 ) towards the mandibular and deep cervical lymph nodes (dcLN) ( 9 , 10 ). Therefore, the meninges is a critical neuro-immunological interface where immune cells are situated to sense threatening factors such as pathogens and antigens ( 7 ).…”
Section: Introductionmentioning
confidence: 99%